Comfort of the elderly in the context of a long-term care facility for the elderly (Research, Society and Development, 2020)
Objective: To know the characteristics of the comfort of the elderly in a Long Term Care Facility for the Elderly. Method: Integrative literature review. It was systematized in the Participant strategy, Phenomenon of Interest and Context. The following subjects were identified for search: Participant: Elderly or Institutionalized Elderly, Interest: Comfort, Context: Long-Term Institution for the Elderly. 1.994 documents were identified, four studies selected. Results: Two categories emerged: the relationship with the “I”, which is autonomy, independence, self comfort, respect for privacy, the practice of religiosity, and the relationship with the “other” made effective through affection, meeting individual needs, relationship with the staff, security, respect for privacy. Conclusion: The comfort characteristics of the elderly in a Long Term Care Facility for the Elderly presupposes subjectivity and objectivity, which must be incorporated into comforting nursing interventions.